IL-12 and Mucosal CD14(+) Monocyte-Like Cells Induce IL-8 in Colonic Memory CD4(+) T Cells of Patients With Ulcerative Colitis but not Crohn’s Disease - Chapuy, Laurence (J Crohns Colitis, 2020)
BACKGROUND AND AIMS: CD14(+) mononuclear phagocytes [MNPs] and T cells infiltrate colon in ulcerative colitis [UC]. Here we investigated how CD14(+) MNPs and the cytokines they produce shape the colonic effector T cell profile. METHODS: Colonic or mesenteric lymph node [mLNs] CD4(+) T cells isolated from UC or Crohn’s disease [CD] patients were stimulated with cytokines or autologous CD14(+) MNPs. Cytokine expression was assessed by intracytoplasmic staining and multiplex ELISA. Unsupervised phenotypic multicolour analysis of colonic CD14(+) MNPs was performed using the FlowSOM algorithm. RESULTS: Among CD14(+)CD64(+)HLA-DR(+)SIRPα (+) MNPs, only the pro-inflammatory cytokine-producing CD163(−) subpopulation accumulated in inflamed UC colon and promoted mucosal IL-1β-dependent Th17, Th17/Th1, Th17/Th22 but not Th1 responses. Unsupervised phenotypic analysis of CD14(+)CD64(+) MNPs segregated CD163(−) monocyte-like cells and CD163(+) macrophages. Unexpectedly, IL-12, IL-1β and CD163(−), but not CD163(+), cells induced IL-8 expression in colonic CD4(+) T cells, which co-expressed IFN-γ and/or IL-17 in UC and not CD. The CD163(−) monocyte-like cells increased the frequency of IL-8(+)IL-17(+/−)IFN-γ (+/−) T cells through IL-1β and IL-12. Finally, colonic IL-8(+) T cells co-expressing GM-CSF, TNF-α and IL-6 were detected ex vivo and, promoted by IL-12 in the mucosa and mLNs in UC only. CONCLUSIONS: Our findings established a link between monocyte-like CD163(−) MNPs, IL-12, IL-1β and the detection of colonic memory IL-8-producing CD4(+) T cells, which might all contribute to the pathogenesis of UC.